The extent of the legitimacy of the use of drones according to the international humanitarian law and International human rights law - عجيل زينة; مايا شوكت صفطلي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
In light of rapid increase and development of the use of drones for military and intelligence purposses and in light of the absence of an international legal framework vegulating their use and based on the growing controversy and the growing fears of expanding the use of these weaponse during international or non-conflicts , or to carry out assassinations or targeted killing outside war zones and traditional conflicts. The associated threat to democratic values such as the absence of account ability , trans pavency and the rule of law. As well as the increase in civilian casualties caused by these drones , in addition to violating the international legal framework regulating military operations and violating international human rights covenants. Since international law may not be sufficiently equipped to frame the use of rapidly developing technology that may cause the deaths of hundreds of civilians , it is necessary to address the range of challenges that have arisen from these technological developments and to assess the humanitarian consequences of now weapons technologies before they are developed and used.